2012
DOI: 10.1097/shk.0b013e31826b64e5
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory Effects of Selective Receptor Blockade During Hemorrhagic Shock Treatment With Vasopressin

Abstract: Hemorrhagic shock is a major cause of death in modern societies. Some patients, when treated, fail to sustain normal cardiovascular parameters, requiring fluid therapy and vasoactive drugs. Among drugs with cardiovascular profile other than catecholamine, vasopressin (VP) is emerging as an option. To better understand its effects during hemorrhagic shock, we compared the effects of VP and noradrenaline (NA), associated to fluid therapy. In this work, hamsters were subjected to shock by withdrawal of 40% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 24 publications
0
20
0
2
Order By: Relevance
“…Other non-fluid-based agents with vasoactive properties showed conflicting results. Neither vasopressors 20,57,60,61 nor vasodilators 42,55,59,60 were effective in the preclinical setting. One of the studies investigating the effect of vasopressin reported a decrease in blood flow and an increase in capillary leak as a result of the given treatment, 61 while another study reported no effect of vasopressin on blood flow.…”
Section: Vasoactive Agentsmentioning
confidence: 98%
See 2 more Smart Citations
“…Other non-fluid-based agents with vasoactive properties showed conflicting results. Neither vasopressors 20,57,60,61 nor vasodilators 42,55,59,60 were effective in the preclinical setting. One of the studies investigating the effect of vasopressin reported a decrease in blood flow and an increase in capillary leak as a result of the given treatment, 61 while another study reported no effect of vasopressin on blood flow.…”
Section: Vasoactive Agentsmentioning
confidence: 98%
“…19,42,[52][53][54][55] Eleven vasoactive agents (58%) did not affect blood flow. 19,22,[56][57][58][59][60] The remaining two studies (10%) reported a decrease in blood flow, 61 or results varied markedly between organs. 20 Vasopressin showed contrasting results with a decrease in intestinal blood flow, 61 but no effect on dorsal blood flow.…”
Section: Vasoactive Agents (N = 19)mentioning
confidence: 99%
See 1 more Smart Citation
“…There were multiple studies that used drug delivery as interventions (rather than purely comparing different fluids), including additives (108)(109)(110)(111), noradrenaline (112), polydatin (113), nitric oxide (114) and naloxone (115).…”
Section: Notable Exclusionsmentioning
confidence: 99%
“…Lors du choc hémorragique, chez le hamster, après remplissage vasculaire, la vasopressine améliore les paramètres de microcirculation et d'interaction leucocytes-endothé-lium, via son récepteur V2 (vasodilatation avec redistribution du flux sanguin dans la microcirculation) [58]. Chez le chien, l'administration de vasopressine, sans remplissage vasculaire ou transfusion sanguine associés, induit une dété-rioration des paramètres de l'hémodynamique systémique (absence d'amélioration du débit cardiaque) et de la microcirculation conjonctivale (diminution du diamètre des veinules et de la vélocité des globules rouges) [48].…”
Section: Effets De La Vasopressine Sur La Microcirculation Chez L'animalunclassified